Colonialismo, administração e iluminismo: história da administração pública colonial e imperial - Araujo , Marcos Dias de (2021)
In studies of the history of administration, the emphasis persists on the period from 1930 onwards when rational administration would have been implemented in the state and in large-scale companies. The present research turns to colonial Brazil, a period far from that, to show the first moments of rationalization and change of perspective of the traditional ways of administering public affairs. Methodologically, the study is configured as a bibliographical historiographical research to understand the initial structures of colonization and its establishment in different American territories. With the illustration and the Pombaline government, the administration of the Portuguese Empire becomes a tension between the illustrated rationalization and the previous power relations. Pombaline letters and documents were studied showing this attempt to moralize, organize and train better servants who would serve as an example for their conduct to other employees. At the end of the work, the duration of this Pombaline formation and the consequent tension with the local powers in the beginning of the Brazilian Empire until 1844, when an exclusively Brazilian and trained generation with a bureaucratic body emerges. We conclude the thesis defending the idea that administrative rationalization did not start in the 20th or 19th century, but in the 18th, in a slow spiral that culminated in the late efforts to fight local corruption and to train employees better prepared to deal with the challenges of the capitalist and technological world of the 19th and 20th century.